2003
DOI: 10.1038/nature01895
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear cataract caused by a lack of DNA degradation in the mouse eye lens

Abstract: The eye lens is composed of fibre cells, which develop from the epithelial cells on the anterior surface of the lens. Differentiation into a lens fibre cell is accompanied by changes in cell shape, the expression of crystallins and the degradation of cellular organelles. The loss of organelles is believed to ensure the transparency of the lens, but the molecular mechanism behind this process is not known. Here we show that DLAD ('DNase II-like acid DNase', also called DNase IIbeta) is expressed in human and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
159
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(169 citation statements)
references
References 25 publications
7
159
2
1
Order By: Relevance
“…7) DLAD has been found in mammals, and is reported to be expressed in the mouse lens, liver and human lens, salivary glands, and lungs. 8,9) In this study, we showed that DLAD mRNA was expressed in the lens, brain, lung, liver and pancreas in rats. In particular, stronger DLAD mRNA bands were found in the lens and liver (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…7) DLAD has been found in mammals, and is reported to be expressed in the mouse lens, liver and human lens, salivary glands, and lungs. 8,9) In this study, we showed that DLAD mRNA was expressed in the lens, brain, lung, liver and pancreas in rats. In particular, stronger DLAD mRNA bands were found in the lens and liver (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…These include genetic factors, diabetes, smoking, nutrition, the cumulative effect of X-rays, ultraviolet irradiation, and alteration in both endocrine and enzymatic equilibrium. [26][27][28][29][30][31] Recently, Nishimoto et al 9) reported that DLAD in the lens played an essential role in the degradation of nuclear DNA, and a lack of the DLAD gene causes nuclear cataracts. DLAD appears to be a divergent form of DNase II that catalyzes the hydrolysis of DNA into oligonucleotides under acidic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apaf1 knockout mice have abnormal lens epithelium differentiation and inhibition of apoptosis in their lenses (Cecconi et al, 1998). DNase II-like acid DNase deficiency in mice produced congenital cataract formation with undigested DNA during lens differentiation (Nishimoto et al, 2003). Missense mutation of aA-crystallin (HspB4) and aB-crystallin was found in familiar congenital cataracts (Table 1).…”
Section: Molecular Chaperones In Degenerative Diseasesmentioning
confidence: 99%
“…Unlike DNase II, which is ubiquitously expressed in various tissues and cells, DLAD is specifically expressed in fiber cells of the optic lens (Fig. 3) (Nishimoto et al 2003). This avascular tissue, which focuses light onto the retina, consists of packed fiber cells bounded at the anterior by a monolayer of epithelial cells.…”
Section: Dlad a Dnase In Lens Fiber Cellsmentioning
confidence: 99%